PENGARUH PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS-ACHIEVEMENT DIVISIONS (STAD) KIMIA TERHADAP KEAKTIFAN DAN HASIL BELAJAR SISWA KELAS XI IPA SMA NEGERI 1 MANOKWARI - Nelly, .; Siregar, Tiurlina (Jurnal Ilmu Pendidikan Indonesia, 2014)
This research is quasi research which its aim to see the influence of using cooperative learning Method Student Teanis Achievement to activity and student learning result. The population of this research are students grade XI sains one to grade XI sains five in SMA 1 Manokwari.. The research result so learning with using cooperative method STAD can increase learning result in reaction rate material than convensional learning. The angket analyze of activity show that experiment class and control class. Give respon to the influence method STAD and convensional each of them are 80 % and 60,94 %. Keyword : Cooperative Learning Method Student Teams Chievement Divisions (STAD), The activity, Learning Outcomes.